Sintesis Katalis Ni/ZSM-5 untuk Pirolisis Cangkang Sawit Menjadi Bio-Oil - Sunaro Sunarno (Eksergi)
Increasing of the palm plantation every years can be increase the Crude Palm Oil (CPO) product, effecting the increase of the palm solid waste . One of the solid waste is palm kernel shell which used as energy source for boiler that produce palm ash wich as substant for the synthesis of ZSM-5catalyst (ratio Si/Al= 30). The synthesis of Ni/ZSM-5 by impregnation method at temperature 900 C, for 6 hours, then calcined by the themperature various of 4000 C, 5000 C, and 6000 C during 4 hours with nitrogen gas is flow, and followed by oxidation with oxygen gas and reduction with hydrogen gas flow for 2 hours at themperature 4000 C have been conducted. The resulting Ni/ZSM-5 was analyzed by BET method and applied for pyrolysis proccess of the palm kernel shell to produce bio oil. The bio oil product was charactrized for dencity, viscocity and flash point. The result show that maximum surface area of catalyst forcalcination obtained at 500ºC is 67,874 m2 /g, and study of pyrolysis proccess from 1% mass of palm kernel shell produce of 43% bio oil yield. The characterization result of bio-oil obtained that density is 0.954gr/ml, viscosity is 12.65cp, and flash point is 62o C.